Answer:
2 Paul's Survey sample only included tenth graders
Step-by-step explanation:
The reson why this is your answer is simple
Because this is true, he ONLY surveyed tenth-graders. He should have found for all of the students, including the other 1,100 students that didn't get surveyed.
Thanks!
8x + 6 - 2x = 34x
Simplify 8x +6 - 2x to 6x + 6:
6x + 6 = 34x
Subtract 6x from both sides:
6 = 34x- 6x
Simplify 34x - 6x to 28x:
6 = 28x
Divide both sides by 28:
![\frac{6}{28}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B28%7D%20)
= x
Simplify
![\frac{6}{28}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7B28%7D%20)
to
![\frac{3}{14}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B14%7D%20)
:
![\frac{3}{14}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B14%7D%20)
= x
Now switch sides and the answer is:
x =
![\frac{3}{14}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3%7D%7B14%7D%20)
:) <3
<span>-10
-(100) ^1/2
</span><span>100 ^1/2 </span>
Answer:
x = 2.
Step-by-step explanation:
Solve for x:
0.3 (4 - x) = x - 1.4
Expand out terms of the left hand side:
1.2 - 0.3 x = x - 1.4
Subtract x from both sides:
1.2 + (-0.3 x - x) = (x - x) - 1.4
-0.3 x - x = -1.3 x:
-1.3 x + 1.2 = (x - x) - 1.4
x - x = 0:
1.2 - 1.3 x = -1.4
Subtract 1.2` from both sides:
(1.2 - 1.2) - 1.3 x = -1.2 - 1.4
1.2 - 1.2 = 0:
-1.3 x = -1.2 - 1.4
-1.2 - 1.4 = -2.6:
-1.3 x = -2.6
Divide both sides of -1.3 x = -2.6 by -1.3:
(-1.3 x)/(-1.3) = (-2.6)/(-1.3)
(-1.3)/(-1.3) = 1:
x = (-2.6)/(-1.3)
(-2.6)/(-1.3) = 2.:
Answer: x = 2.